2017
DOI: 10.1155/2017/8073798
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress Regulation on Endothelial Cells by Hydrophilic Astaxanthin Complex: Chemical, Biological, and Molecular Antioxidant Activity Evaluation

Abstract: An imbalance in the reactive oxygen species (ROS) homeostasis is involved in the pathogenesis of oxidative stress-related diseases. Astaxanthin, a xanthophyll carotenoid with high antioxidant capacities, has been shown to prevent the first stages of oxidative stress. Here, we evaluate the antioxidant capacities of astaxanthin included within hydroxypropyl-beta-cyclodextrin (CD-A) to directly and indirectly reduce the induced ROS production. First, chemical methods were used to corroborate the preservation of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 91 publications
3
23
0
Order By: Relevance
“…In this regard, the capacity of NLC to amplify antioxidant activity was also shown by Nayyer Karimi et al [ 16 ] using DPPH test to evaluate turmeric-NLC scavenging activity compared to free turmeric extract. Furthermore, these results are supported by those obtained in our previous work showing the enhancing of astaxanthin antioxidant capacity by hydroxypropyl-beta-cyclodextrin complexation [ 34 ].…”
Section: Resultssupporting
confidence: 87%
“…In this regard, the capacity of NLC to amplify antioxidant activity was also shown by Nayyer Karimi et al [ 16 ] using DPPH test to evaluate turmeric-NLC scavenging activity compared to free turmeric extract. Furthermore, these results are supported by those obtained in our previous work showing the enhancing of astaxanthin antioxidant capacity by hydroxypropyl-beta-cyclodextrin complexation [ 34 ].…”
Section: Resultssupporting
confidence: 87%
“…137 Zuluaga recently reported that the generation of ROS induced by stressors (AAPH and t-BuOOH, which are free radical donors that generate a burst of ROS) upregulates PTEN gene expression, which causes cellular apoptosis by deactivating AKT. 138 Conversely, astaxanthin treatment significantly suppressed PTEN expression and reduced both eNOS and Bax gene expression in endothelial cells under oxidative stress. 138 Astaxanthin can activate the PI3K/Akt pathway, protecting against H 2 O 2 -induced oxidative stress through the Nrf2/ARE pathway in ARPE-19 cells.…”
Section: Pi3k/akt Pathwaymentioning
confidence: 98%
“…138 Conversely, astaxanthin treatment significantly suppressed PTEN expression and reduced both eNOS and Bax gene expression in endothelial cells under oxidative stress. 138 Astaxanthin can activate the PI3K/Akt pathway, protecting against H 2 O 2 -induced oxidative stress through the Nrf2/ARE pathway in ARPE-19 cells. 139 Astaxanthin activates the specificity protein 1 (Sp1) and NMDA receptor subunit 1 (NR1) signalling pathway, inhibiting the upregulation and nuclear transfer of Sp1 Figure 3 Proposed mechanism by which astaxanthin inhibits ROS and apoptosis.…”
Section: Pi3k/akt Pathwaymentioning
confidence: 98%
“…Astaxanthin has some a wide range of biological activities such as including antioxidant,anti-inflammatory, anticancer and cardioprotective activities (Wu et al, 2012). Astaxanthin has a strong antioxidant property ( Zuluaga et al,2017). Therefore, In this study, it was aimed to investigate the protective effect of astaxanthin against rat brain injury exposed to cadmium in rats.…”
Section: Introductionmentioning
confidence: 99%